Salsa daddy : dip your way into Mexican cooking - Martínez, Rick (Chef); Beggs, Alex (Copywriter) (Clarkson Potter/Publishers, 2025)
"From the author of Mi Cocina comes a comprehensive (and unbelievably delicous) cookbook that focuses on one of the main pillars of Mexican cuisine: salsas. Featuring 75 salsas and 25 full meal recipes, this cookbook will have you whipping up fresh, enticing spreads in no time. Salsas are both the traditional heart of Mexican cooking-blending charred tomatillos and chiles goes back over five hundred years-and something cooks today can riff most freely, as Rick Martinez, beloved author of Mi Cocina, discovered while tasting a caramelized onion-serrano chile salsa in Mexico City. Salsas make irresistible snacks with chips, of course, but they will also elevate your grilled cheese, your burger, your tacos, or your whole meal. Rick takes us deep into the world of traditional and modern salsas, where a refreshing pico de gallo with oranges and avocados might be chopped up in a few minutes, or where you might simmer chipotles in milk and butter for a creamy, smoky, spicy sauce. With 75 salsa recipes and 25 simple meals that can each be made totally unique by your choice of salsas, this book shows you all the ways salsas can be the heart of your table, too"--